2020
DOI: 10.1093/jn/nxaa125
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Glucose Increases Glucose Absorption and Lipid Deposition via SGLT1/2 Signaling and Acetylated ChREBP in the Intestine and Isolated Intestinal Epithelial Cells of Yellow Catfish

Abstract: ABSTRACT Background Dietary carbohydrate affects intestinal glucose absorption and lipid deposition, but the underlying mechanisms are unknown. Objectives We used yellow catfish and their isolated intestinal epithelial cells (IECs) to test the hypothesis that sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 46 publications
0
35
1
Order By: Relevance
“…Expt 1: in vivo study Experimental procedures. The experimental protocols for fish culture and management have been described in our parallel study (18) . Briefly, yellow catfish from a local fish farm (Wuhan, China) were subjected to a 2-week acclimation in the indoor tanks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expt 1: in vivo study Experimental procedures. The experimental protocols for fish culture and management have been described in our parallel study (18) . Briefly, yellow catfish from a local fish farm (Wuhan, China) were subjected to a 2-week acclimation in the indoor tanks.…”
Section: Methodsmentioning
confidence: 99%
“…Histological and histochemical observation. Haematoxylineosin and Oil Red O stainings were conducted based on our recent publication (18) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal tract is the predominant region of digestion and absorption of carbohydrates and also plays principal roles in glucose transport and metabolism (2) . Generally, glucose from the diet directly or from hydrolysis of other carbohydrates was taken up into the epithelial cells through specific glucose transporters, such as sodium/glucose co-transporters (SGLTs) (2)(3)(4)(5) . Among these SGLTs, SGLT1 and SGLT2 functions as glucose sensors in the intestine, and they transports glucose from the intestinal lumen to the cytosols of enterocytes (3)(4)(5) .…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrate response element binding protein (ChREBP) was a glucose-activated transcription factor (13,14) , and mediated the glucose-induced lipogenesis (15,16) . Many studies have suggested that the function of ChREBP is regulated by translocation from cytoplasm to nucleus and multiple post-translational modifications (5,(17)(18)(19)(20) . Importantly, ChREBP is modified by acetylation, and acetylated ChREBP increases ChREBP transcriptional activity.…”
Section: Introductionmentioning
confidence: 99%